Neuroprotective Effect of Erythropoietin against Pressure Ulcer in a Mouse Model of Small Fiber Neuropathy - Danigo, Aurore; Magy, Laurent; Richard, Laurence; Desmoulière, Alexis; Bourthoumieu, Sylvie; Funalot, Benoît; Demiot, Claire (PLOS ONE, 2014)
An increased risk of skin pressure ulcers (PUs) is common in patients with sensory neuropathies, including those caused by diabetes mellitus. Recombinant human erythropoietin (rhEPO) has been shown to protect the skin against PUs developed in animal models of long-term diabetes. The aim of this work was to determine whether rhEPO could prevent PU formation in a mouse model of drug-inducedSFN. Functional SFN was induced by systemic injection of resiniferatoxin (RTX, 50 µg/kg, i.p.). RhEPO (3000 UI/kg, i.p.) was given the day before RTX injection and then every other day. Seven days after RTX administration, PUs were induced by applying two magnetic plates on the dorsal skin. RTX-treated mice expressed thermal and mechanical hypoalgesia and showed calcitonin gene-related peptide (CGRP) and substance P (SP) depletion without nerve degeneration or vascular dysfunction. RTX mice developed significantly larger stage 2 PUs than Vehicle mice. RhEPO prevented thermal and mechanical hypoalgesia and neuropeptide depletion in small nerve fibers. RhEPO increased hematocrit and altered endothelium-dependent vasodilatation without any effect on PU formation in Vehicle mice. The characteristics of PUs in RTX mice treated with rhEPO and Vehicle mice were found similar. In conclusion, RTX appeared to increased PU development through depletion of CGRP and SP in small nerve fibers, whereas systemic rhEPO treatment had beneficial effect on peptidergic nerve fibers and restored skin protective capacities against ischemic pressure. Our findings support the evaluation of rhEPO and/or its non-hematopoietic analogs in preventing to prevent PUs in patients with SFN.